Working hours in a period of low economic growth - WWWforEurope; Walterskirchen, Ewald (Vienna, 2016)
"Collectively agreed reductions of working hours phased out in Europe in the 1990s. During the last two decades, working time became more flexible and heterogeneous. Working hours of full-time employees in the EU hardly changed. The strong increase in part-time work was the outstanding phenomenon. Today, one third of female employees and almost ten percent of male employees work part-time. In a period of slow growth, productivity gains will be squeezed by subdued investment and low capacity utilisation. Thus, a smaller pie will be available either for real wage increases or for working time reductions. In this situation, it will be politically even more difficult to find an agreement on shorter working hours than in past decades. Since the productivity and employment effects of a working time reduction in a low growth period are quite uncertain, social partners must be willing to negotiate again when the effects become apparent."